STUDENTS’ PERSPECTIVE OF AN IDEAL MEDICAL TEACHER - EXPECTATIONS AND REALITY - Parveen, Zahida (Journal of Ayub Medical College Abbottabad, 2023)
Background: Medical teacher plays an important role in the education of medical students. Medical students always portray their teacher as an ideal. The objective of the study was to find the gap between the best qualities that an ideal medical teacher should have and the best qualities that a medical teacher actually has. Methods: This cross-sectional survey was conducted at Ayub Medical College Abbottabad from April 2021 to Dec 2021. Consented students of 4th year and Final year MBBS were the participants. Data regarding the qualities of the best medical teacher was collected on Likert scaled validated survey questionnaire. Two closed-ended questionnaires were used. Items were the same in both questionnaires. One questionnaire (Questionnaire A) was regarding expectations of students and what qualities they expected in their ideal medical teacher. The second questionnaire (questionnaire B) was about the qualities that a medical teacher actually had been exhibiting that students had experienced. Data was analyzed using SPSS version 22.0. Results: A total of 210 students participated in this study, 126 students were from 4th year and 84 were from the final year of MBBS. Ninety-one and a half percent of students thought that an ideal medical teacher should be competent in his/her subject but in reality, 48% of students reported that their teachers are competent. Ninety-four percent of students rated that an ideal medical teacher should have excellent communication skills but in reality, only 33% reported that their teachers are having good communication skills. Eighty-three (83%) students expect their teachers should be students friendly but in reality, only 22% of teachers are students caring. Eighty-nine percent of students expect that an ideal medical teacher shall demonstrate clinical skills to students but in reality, only 36% experienced demonstration from their teachers. Conclusion: There is a big gap between the expected qualities of a medical teacher and the qualities that a teacher is having in reality from students’ perspectives. Teachers should be trained to bridge this gap,